2000
DOI: 10.1128/jcm.38.11.4152-4159.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Contagious Caprine Pleuropneumonia Using a Mycoplasma capricolum subsp. capripneumoniae Capsular Polysaccharide-Specific Antigen Detection Latex Agglutination Test

Abstract: Latex microspheres (diameter, 8 μm) were coated with anti-Mycoplasma capricolum subsp.capripneumoniae polyclonal immunoglobulin G (IgG) antiserum (anti-F38 biotype). The coated microspheres, when used in a latex agglutination test (LAT), detected M. capricolumsubsp. capripneumoniae antigen in the serum of goats with contagious caprine pleuropneumoniae (CCPP). Beads also agglutinated strongly in the presence of purified M. capricolumsubsp. capripneumoniae capsular polysaccharide (CPS). Preabsorption of CPS-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The first two tests are ranked the least sensitive for confirmation of clinical CCPP cases (+); the third and fourth are suitable (++), and the fifth (+++) is the recommended [ 2 ]. The LAT is considered the simplest, quick and excellent procedure for the “ in field or in situ” diagnosis of CCPP either in whole blood or serum [ 39 ]. Moreover, the LAT is reported to be more sensitive than the CFT [ 40 ] and also easier to perform than the c-ELISA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first two tests are ranked the least sensitive for confirmation of clinical CCPP cases (+); the third and fourth are suitable (++), and the fifth (+++) is the recommended [ 2 ]. The LAT is considered the simplest, quick and excellent procedure for the “ in field or in situ” diagnosis of CCPP either in whole blood or serum [ 39 ]. Moreover, the LAT is reported to be more sensitive than the CFT [ 40 ] and also easier to perform than the c-ELISA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgM is the first to appear and has little specificity which giving risk to pronounced crossreactions, and remains in the blood for short duration, while IgG is produced lately and lasts much longer than IgM antibody isotypes (Staak et al, 2001). The CFT has clear limitations: March et al (2000) observed that 80 to 100% of animals experimentally infected with Mccp in their acute phase were not detected. Based on this report seropositives detected by CF test indicated that there were recent infections and circulation of the causative agent within the flocks.…”
Section: Seroprevalence At Individual Animal Levelmentioning
confidence: 99%
“…Lung samples from one clinical case were positive by PCR (Bölske and others 1996), although no mycoplasmas could be isolated at the time, probably due to recent antibiotic usage. In May 2004, the penside latex agglutination test ( LAT ) (March and others 2000) was seropositive on whole blood samples in five of six goats from a third clinically affected herd, situated 30 km from Kesan.…”
Section: Figurementioning
confidence: 99%